FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PERUSAHAAN NON-KEUANGAN DI BURSA EFEK INDONESIA - SULIANA SULIANA; APIT SUSANTI (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this study is to empirically analyze if life cycle, free cash flow, profitability, firm size, assets growth, market to book ratio, firm leverage and liquidity affect dividend policy of non financial companies in Indonesian Stock Exchange. The data used in this study are obtained from financial statement of non financial companies that listed on Indonesia Stock Exchange, using purposive sampling method. There are 97 samples that meet the criteria. This study uses multiple regression analysis to analyze the hypothesis. The result shows that free cash flow and assets growth affect dividend policy. While life cycle, profitability, firm size, market to book ratio, firm leverage and liquidity do not affect dividen policy.